Wellbeing and Sense of Coherence Among Female Offenders and Non-Offenders: The Importance of Education - Zajenkowska, Anna (The prison journal, 2021)
This article consists of two studies comparing female offenders’ and non-offenders’ wellbeing and sense of coherence. Consistent with the hypotheses in Study 1, the level of general wellbeing was lower among female inmates, but the effect was due to differences in education. In Study 2, the sense of coherence was measured. The results indicated that when education and age are included in the analysis, the coherence levels did not differentiate inmates from non-inmates.